Tissue inhibitor of matrix metalloproteinase-1 role in left atrium matrix remodeling in patients with atrial febrillation - Goryachiy, A. V.; Gozhenko, A. I.; Levchenko, E. M.; Goryachiy, V. V.; Kuznetsova, M. A.; Arapu, M. I. (Journal of Education, Health and Sport, 2017)
Method: TIMP-1 was used as a marker for collagen synthesis. The study group comprised 69 people and the control group 23. Results: Patients with persistent and chronic AF had an elevated level of TIMP-1 in comparison with patients with paroxysmal AF (149.63 + 43.71 ng / ml, 155.90 + 45.86 ng / ml vs 131.51 + 36.92 ng / ml, p <0.001). The level of TIMP-1 was significantly lower in the control group compared to patients with paroxysmal, persistent and chronic AF forms (131.51 + 36.92 ng / ml, 149.63 + 43.71 ng / ml, 155.90 + 45.86 ng / ml and 103.61 + 14.96 ng / ml , P <0.001). Conclusions: The level of TIMP-1 is significantly different between healthy people and patients with AF. Moreover, these markers also differ depending on the shape of the OP. It can be assumed that the intensity of extracellular synthesis and degradation of type I collagen can be related to the severity and type of AF.